Highly-Efficient, Dual-Polarized Huygens’ Metasurfaces for Scan-Angle Enhancement Without Directivity Degradation - Jaemin Kim; Mohammad Soltani; Minseok Kim; George V. Eleftheriades (IEEE Access)
We hereby propose a dual-polarized beam-deflecting metasurface that can double the scan-angle range of a phased-array antenna without compromising the directivity across all scan angles, including broadside. In particular, our research focuses on expanding the scanning range of a dual-polarized phased-array antenna capable of independently steering TE and TM waves. This is achieved by placing a dual-polarized phase-gradient Huygens’ metasurface in front of the antenna. The Huygens’ metasurface employs crossed meander lines in four impedance layers that are suitably optimized to independently control the local electric and magnetic responses for maximizing the transmission for all incident beams. We validate our approach through theoretical analysis, full-wave simulations, and experimental verification. It is demonstrated that the beam-deflecting HMS achieves effective scan range expansion to $-30^{° } \sim 0^{° } $ and $0^{° } \sim 30^{° } $ for TE and TM beams, respectively, using a dual-polarized phased array antenna source that scans from −15° and 15°.